Creative economy assessment: a case study of Kish Island. Issue 12 (4th December 2017) - Lafzi Ghazi, Elham; Goede, Miguel
Abstract : Purpose: The purpose of this paper is to evaluate the case of Kish, which is a small island off the coast of Iran, using the creative indicators of a creative economy. Design/methodology/approach: Based on the extant literature, a set of performance measures and factors are identified for the creative economy. This set is mainly based on Florida's theory on the creative class. The case of Kish Island is evaluated based on these indicators, and after analysis, conclusions are drawn. Findings: Kish Island, with its numerous tourist attractions, shows remarkable creative industries that highlight the presence of the creative class and the development of a creative economy in this area. Originality/value: The paper illustrates the model of a creative economy assessment for the small Kish Island and finally provides a good understanding of the concept of the creative economy as a key element of the creative city.